AI Driven Crop Disease Prediction and System Management - DR.A.Meippane; Charumathy B; Moshika I; kaviya L; Parameswari D (The Bioscan, 2026)
The Ai-Driven Crop Disease Prediction and Management System is a mobile application designed to help home gardeners, hobbyists, and small-scale crop managers identify and manage the plant disease effectively. Built using Flutter, the application allows users to capture or upload images of diseased plant leaves, which are analyzed using advanced Artificial Intelligence(AI) and Machine Learning(ML) algorithms to diagnose the disease. The system provides instant reports with disease details, causes, and tailored treatment recommendations, including medication, natural remedies, and preventive measures. Additionally, the application detects the current temperature and soil humidity, offering real-time insights into environmental conditions. It sends notifications when temperature or humidity levels deviate from optimal ranges for specific plants, enabling users to take timely actions to maintain plant health. Leveraging a specific dataset of plant images, the system ensures high accuracy in disease diagnosis and promotes sustainable gardening practices by reducing the reliance on harmful chemicals. This AI-driven solution empowers users to make informed decisions about plant care, contributing to healthier plants and more vibrant gardens.